Extraordinary events, disasters and marching armies in greater Poland in the 17th and 18th centuries and their impact on the life of nuns in the Benedictine monastery as reflected in the monastic Chronicle - Lewandowska, Ada (Saeculum Christianum. Pismo Historyczne, 2021)
The Benedictine Monastery in Poznań was founded in 1607 by Magdalena Mortęska, the reformer of the religious order. By analysing the monastic chronicles, the author wanted to show the influence of extra-ordinary events in Greater Poland and Poznań in the 17th and 18th centuries on the life of enclosed nuns. The article describes what changed when people visited the monastery, what life of nuns looked like during epidemics, floods and other disasters that took place in Greater Poland. The article moreover probes the influence of wars and the presence of foreign armies in the city of Poznań on the life of the Benedictine nuns.